Technology Management in Lean Manufacturing Implementation: A Case Study - Nordin, Norani; Othman, Ghazali (2014)
The demanding of globalization and the concern to remain competitive in the global economy has driven countries to actively pursue high-technology and knowledge-intensive service in industrialization strategies. To encourage the development of industrial technology, several factors must be considered such as knowledge, skills, technical development and basic infrastructure. This study attempts to investigate the technology management required in implementing lean manufacturing system in a manufacturing company. This system is useful to ensure production process in operation smoothly run without interrupted. A single-case study was employed. The three different methods for data gathering: interview, observation and documents all contributed towards the data analysis. The respondents were asked about their experience in implementing lean manufacturing in the company and also the challenges occurred. The results from the case study show that to implementing a new technology, commitment from all employees in the organization is crucial. Management also should analyze and predict the potential failure as a preparation before starting to adopt the new technology in the organization